Integrating Islamic Psychological Principles in Enhancing Students' Academic Resilience - Aprilianti, Eka (Utan Kayu Publishing, 2024)
This study examines the concept of resilience within the context of Islamic psychology, an area relatively unexplored by conventional psychological approaches. Employing qualitative methodology, particularly document review, this research aims to understand how principles documented in the Quran and Hadith can influence individual resilience in facing academic stress and challenges. The data analysis process involves data reduction, display, and conclusion drawing, emphasizing validation through credibility, transferability, dependability, and confirmability of results. Key findings indicate that the practical application of Islamic values enhances academic resilience, reflected in individuals’ resilience when facing academic tasks. This study provides new insights into educational psychology by offering an alternative perspective that integrates spiritual dimensions into education. This enriches our understanding of resilience, while also making a significant theoretical contribution to the development of modern educational paradigms. By exploring the methods of Islamization of knowledge, this study also delves into aspects of resilience rooted in Islamic values, providing constructive solutions to criticisms of modern psychology often considered detached from divine values. The practical implications of this research are expected to support more effective mentoring and teaching efforts in value-based educational contexts.